(Re)theorising More-than-parental Involvement in Early Childhood Education and Care - Sadownik, Alicja R.; Višnjić Jevtić, Adrijana (International Perspectives on Early Childhood Education and Development, 2023)
This open access book provides a critical, thought-provoking, and stimulating overview of theories applied worldwide to conceptualise collaborations between early childhood education and children's families. The book starts with a critical reflection on the colonial undertones of parental involvement (PI) and acknowledges a strong political will to improve this aspect of early childhood education and care. The chapters in the book describe and discuss various theories, including the cultural historical wholeness approach, Bronfenbrenner's ecology of human development, the theory of social capital, the theory of collaboration, family-school partnership models proposed by Epstein and Hornby, Bourdieu's social theory, the theory of practice architectures, the discourse/narrative theory, and posthumanism. By proposing the concept of more-than-parents, the authors aim to embrace both the diversity of intergenerational family configurations and the agency of materiality, artifacts, and the involvement of more-than-human actors.